Phantasus, a web application for visual and interactive gene expression analysis - Kleverov, Maksim; Zenkova, Daria; Kamenev, Vladislav; Sablina, Margarita; Artyomov, Maxim N; Sergushichev, Alexey A (eLife, 2024)
Transcriptomic profiling became a standard approach to quantify a cell state, which led to the accumulation of huge amount of public gene expression datasets. However, both reuse of these datasets or analysis of newly generated ones requires significant technical expertise. Here, we present Phantasus: a user-friendly web application for interactive gene expression analysis which provides a streamlined access to more than 96,000 public gene expression datasets, as well as allows analysis of user-uploaded datasets. Phantasus integrates an intuitive and highly interactive JavaScript-based heatmap interface with an ability to run sophisticated R-based analysis methods. Overall Phantasus allows users to go all the way from loading, normalizing, and filtering data to doing differential gene expression and downstream analysis. Phantasus can be accessed online at https://alserglab.wustl.edu/phantasus or can be installed locally from Bioconductor ( https://bioconductor.org/packages/phantasus ). Phantasus source code is available at https://github.com/ctlab/phantasus under an MIT license.